Numerical Simulation of Impact Loads of Main Fan Blades in Gas Explosion - Jianliang Gao; Jingzhang Ren; Xuebo Zhang; Jiajia Liu; Chunxia Wang (Shock and Vibration)
The shock wave generated by a severe gas explosion accident can damage the main fan, and the toxic and harmful gases in the well cannot be discharged in time, leading to the expansion of disaster accidents. Therefore, it is meaningful to study impact loads of main fan blades in gas explosion. In this paper, a full-scale three-dimensional numerical simulation model has been established based on No. 2 Yangchangwan Coal Mine in China. The propagation of shock wave in shaft and air tunnel and the dynamic process of main fan blade subjected to shock load when gas explosion of different volume occurs in heading face have been simulated. The overpressure on the blade at different times, the overpressure distribution on the blade, and the relationship between the overpressure and the explosion intensity have been obtained. The results showed that the time when the explosion shock wave reached, each blade of the wind turbine was basically the same, and the time when each blade reached, the maximum overpressure was basically the same. With the increase of gas explosion volume, occurrence time of overpressure and maximum overpressure time on the fan blade were shortened, and the time interval between them was also shortened. There is a little difference in the overpressure of each blade. Fan blade directly above the hub was subject to the highest overpressure, and fan blade directly below the hub was subject to the lowest overpressure. The overpressure of the maximum overpressure blade was 5.44% to 6.77% higher than that of the minimum overpressure blade. The distribution of overpressure on each fan blade was uneven, and the overpressures on blade edges were the lowest. The overpressure on the fan blades showed a corrugated distribution along the radial direction. There was 12.06% to 15.40% difference between the maximum and minimum overpressure section on the fan blade.